Self-Construction and the Imagination in the Drama of Lope de Vega and Cervantes. Issue 7 (13th September 2016) - Henry, Melanie; Thacker, Jonathan
Abstract: In their mature drama Lope de Vega and Cervantes each produced characters of some sophistication. In spite of the conclusions of some scholars, both playwrights were able to imagine, create and sustain the illusion of character depth and development on stage. However, they did this in distinct ways and with differing aims. In this article we examine the ways characters are created and are seen to develop in the two dramatists' work (using El castigo sin venganza and La entretenida as examples of their practice). In particular we are interested in the role of the imagination in this process: characters' use and exploitation of earlier visual, poetic and dramatic models; the creation of theatre within theatre; the power of pre-existing images in self-construction; and the clash of the imaginary and the real world. Although it is common enough to contrast the popular theatre of Lope with the more overtly experimental Cervantes, this article moves beyond the antagonistic confines of the Lope/Cervantes debate to compare in depth their techniques of characterization.